SUMBER DAYA MANUSIA INDONESIA MENGHADAPI ERA GLOBALISASI EKONOMI DITINJAU DARI SEGI PEMERATAAN - Kertopati, Ton (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2004)
Most Indonesians would agree that the Indonesian enterprises should definitely play a more efficient role in the global economy. However, the argument that insist on the quality of human resources.  Even if the government was  willing to commit to a comprehensive programs.                                   .While attempt to improve  educational programs through internal restructuringmay  be a  valid concept.  The present  culture in  government means  it is  toimplement reforms successfully.The willingness and the capacity to approach the capacity of human resourcesfor change to face _gn economical global problems